Case Study: Mechanism for Increased Follicular Helper T Cell Development in Activated PI3K Delta Syndrome - Thauland, Timothy J.; Pellerin, Laurence; Ohgami, Robert S.; Bacchetta, Rosa; Butte, Manish J. (Frontiers in Immunology, 2019)
Gain-of-function variants in p110δ, the catalytic subunit of phosphatidylinositol 3-kinase (PI3K) expressed in lymphocytes, cause activated PI3-kinase δ syndrome (APDS), a primary immunodeficiency that is characterized by recurrent infections, viremia, lymphadenopathy, and autoimmunity. The mechanism of autoimmunity in APDS has not been well understood. Here, we show the profound skewing of peripheral CD4+ T cells to a T follicular helper (TFH) phenotype in a patient with APDS bearing a novel p110δ variant, Y524S. We also saw a diminishment of transient Foxp3 expression in activated T cells. Mechanistic studies revealed that both the new variant and a previously described, pathogenic variant (E81K) enhanced an interaction between intracellular Osteopontin and p85α. This interaction had been shown in mice to promote TFH differentiation. Our results demonstrate a new influence of PI3K on human T cell differentiation that is unrelated to its lipid-kinase activity and suggest that TFH should be monitored in APDS patients.